The acquisition of grade alternation in North Saami - Bals, Berit Anne (Universitetet i Tromsø, 2004)
In special issue: Tromsø Working Papers in Language Acquisition This paper looks at how the North Saami grade alternation system develops in children. Grade alternation is a morphophonological process, in which foot-medial consonants alternate between two forms, the strong and the weak grade. There are qualitative alternations, quantitative alternations and in some patterns, both the length and quality of the consonants alternate. These alternations happen in the declension of nouns and the conjugation of verbs. Some case forms of nouns and some forms of verbs are connected to the strong grade, whereas others are connected to the weak grade.The task with which children are faced, is to learn all the different phonological alternations and to connect them to morphology. This paper focuses on the order of acquisition of the various patterns, and on the types of mistakes that children make. We show that the type of alternations to be acquired first are quantity alternations, in which the length of the consonants alternates. The next patterns to be acquired are qualitative alternations, such as devoicing. In the third stage, children learn to combine qualitative and quantitative alternations, such as in deglottalization with nasal legthening. The last patterns to be acquired are patterns with complex foot medial consonants or consonant clusters. The article argues that children´s errors are purely phonological. Connecting the alternations to morphology happens early in the development, and that the remaining errors have to do with the complexity of the phonological alternation.